Advancing gonadal development and maturity by ovaprim in Labeo rohita (Ham.) - Kumar, Anup; Singh, A K; Singh, I J; Ram, R N (Indian Journal of Fisheries, 2011)
Effect of ovaprim on acceleration of developmental and maturational processes in the gonads of Labeo rohita has been studied during pre-spawning phase of its annual reproductive cycle. Two intramuscular injections of ovaprim given @ 0.1 ml/kg body weight fortnightly during early pre-spawning phase (April) induced increase in gonadosomatic index (GSI) of both male and female specimens of L. rohita. The lipid content in testis and liver decreased significantly in ovaprim treated male fish. Changes in hepatosomatic index (HSI), water content in gonads and liver of both sexes and lipid content in ovary and liver of female treated with ovaprim were not significant. Advance stages of oocyte with vitellogenic activity in female and augmented spermatogenic activity in male specimens were observed after treatment with ovaprim. Increased biosynthetic activities in hepatocytes of both sexes of L. rohita, evident by cytoplasmic characteristics and enlarged nuclear size were also apparaent. These observations indicate that optimized dose and frequency of ovaprim, widely used for inducing spawning in majority of fishes, has the potential of advancing gonadal development and maturity in L. rohita during pre-spawning phase of its annual reproductive cycle